Characterization of Coke-Making Coals of High Reactivity from Northwest China - Qiang Wu; Zizong Zhu; Guojing Shi; Feng Wang; Yangyang Xie (The Minerals, Metals and Materials Society, 2018)
The coal chars from northwestern part of China are characterized with high reactivity and low strength after reaction. Four type of coke-making coals selected from northwestern part of China were studied by proximate analysis, ultimate analysis, vitrinite reflectance analysis, and FTIR with curve-fitting analysis to obtain information on their chemical composition and chemical structure. The results show that the studied coals have relatively high values of final contraction of coke residue index (x) and relatively low values of maximum thickness of plastic layer (y) and average vitrinite reflectance. Based on the curve-fitting analysis of FTIR spectra, the aliphatic carbon (Cal), the aromatic carbon (Car), and the molecular structural parameters such as CH2/CH3, fa, Hal/Har, and (R/C)u are determined. The results of curve-fitting analysis indicate that the studied coals are characterized by a large amount of oxygen-containing functional groups and aliphatic side chains.